Web-based Secure Degree Certificate Legalization System Using Advanced Encryption Standard Algorithm - Henny Indriyawati; Titin Winarti; Vensy Vydia (Universitas Kristen Satya Wacana, 2024)
Degree certificate legalization system with encryption security feature using Advanced Encryption Standard (AES) in Semarang University has a purpose to support academic to do online document legalization through a system. The main problem which occurs in academic administration is a long document legalization process that causes an ineffective and inefficient legalization process. To solve the problem, a system that can encrypt a document for better security is required. This system is built with the Advanced Encryption Standard algorithm with a 128-bit sized key to encrypt confidential information inside the document. During the encryption process, this algorithm operates using 4x4 bit array blocks and passing many encryption processes for at least 10 (ten) times. The application is analyzed with object-oriented analysis and modeled with Unified Modeling Language. The result of this research is a system which can secure document with AES algorithm with a 256-bit sized key. The security element in this algorithm will make easier to identify the owner of the document. The secured document is easily accessible through PHP-based web or available QR code. When decrypting the document, the application will activate the camera function and decrypt the information document.